HUBUNGAN KELENTUKAN OTOT PUNGGUNG DAN DAYA LEDAK OTOT TUNGKAI TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS XI SMK TIGAMA PEKANBARU - Richi Reza Putra Reza Putra; Saripin '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : This examination was done with using colleration examination design that has goal to investigate how far variables ( back muscle flexibility and limb muscle explosive power ) at once factor that hooked with other factors ( result high jump ). In this examination population that was used pekanbaru tigama senior high school xi grade male students. The population in this examination as much 25 people. For result waist muscle flexibility examination as much 25 samples, 3 people ( 12% ) have waist muscle flexibility with value range 14,40 -15,53 , than 5 people ( 20% ) have waist muscle flexibility with value range 15,54 – 16,67 , next 3 people (12% ) have waist muscle flexibility with value range 16,68 – 17,81 , whereas 5 people ( 20% ) have waist muscle flexibility with value range 17,82-18,95 , and 7 people ( 25% ) have waist muscle flexibility with value range 18,96-20,09 , and the last 2 people (8% ) have waist muscle flexibility with value range 20,10-21,23. For result limb muscle explosive power examination as much 25 samples, 1 people (4%) have limb muscle explosive power result with value range 1.10-1.27, than 4 people (16% have limb muscle explosive power result with value range 1.28-1.45, next 2 people (8%) have limb muscle explosive power result with value range 1.46-1.63, whereas 9 people (36%) have limb muscle explosive power result with value range 1.64-1.81, and 6 people (24%) have limb muscle explosive power result with value range 1.82-1.99, the last 3 people (12%) have limb muscle explosive power result with value range 2.00-2.17. F,or result squat model high jump examination as much 25 samples, 2 people (12%) have high jump result with value range 3.20-3.38, than 4 people (16%) have high jump result with value range 3.39-3.57, next 2 people (8%) have high jump result with value range 3.58-3.76, whereas 10 people (40%) have high jump result with value range 3.77-3.95, and 6 people (24%) have high jump with value range 3.96-4.14, the last 1 people (4%) have high jump with value range 4.15-4.33. Keywords : Back Muscle Flexibility, Limb Muscle Explosive Power, Squat Model High Jump